2022
DOI: 10.1002/mp.15629
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of trabecular bone microstructure using CT imaging and continuum mechanical modeling

Abstract: Purpose Osteoporosis is a bone disease associated with enhanced bone loss, microstructural degeneration, and fracture‐risk. Finite element (FE) modeling is used to estimate trabecular bone (Tb) modulus from high‐resolution three‐dimensional (3‐D) imaging modalities including micro‐computed tomography (CT), magnetic resonance imaging (MRI), and high‐resolution peripheral quantitative CT (HR‐pQCT). This paper validates an application of voxel‐based continuum finite element analysis (FEA) to predict Tb modulus fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Though, voxel-based mesh is inherently applicable to simpler geometries with plane boundary surfaces, a recent study 29 shows sufficient accuracy for curved surfaces when using high resolution mesh. In literature, voxel-based mesh has been efficiently used to model bone failure, 30,31 topology optimization, 32 simulation of material microstructures 33,34 and manufacturing processes 35 to name a few. Since voxel-based mesh consume very less memory, along with matrix-free strategy and GPU acceleration, it is a promising alternative for large-scale elastoplasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Though, voxel-based mesh is inherently applicable to simpler geometries with plane boundary surfaces, a recent study 29 shows sufficient accuracy for curved surfaces when using high resolution mesh. In literature, voxel-based mesh has been efficiently used to model bone failure, 30,31 topology optimization, 32 simulation of material microstructures 33,34 and manufacturing processes 35 to name a few. Since voxel-based mesh consume very less memory, along with matrix-free strategy and GPU acceleration, it is a promising alternative for large-scale elastoplasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, emerging whole-body CT scanners have drawn interest as an alternative to HR-pQCT and MRI for in vivo bone micro-imaging at peripheral sites due to their widespread availability in clinical setting, high-resolution, fast scan-speed, and ultra-low radiation (Chen et al 2018 ). In an ex vivo study, (Bauer et al 2014 ) computed failure loads of small cadaveric Tb specimens using CT-based FEA, where bone voxels were separated from marrow by thresholding and a constant Young’s modulus was used for bone voxels in an oriented brick mesh model (Guha et al 2022 ) established a nonlinear continuum FEA method for in vivo ankle CT scans that computes Tb microstructural strength without requiring separation of Tb micro-network from marrow space, while capturing the impacts of micro-distribution of bone mineral on strength. Relaxation of the segmentation of Tb microstructure by Guha et al ’s method allows FEA-based study of bone strength at relatively low-resolution (LR) imaging frequently available in routine clinical scans, while accounting for bone micro-distribution at the level of Tb network.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge with CT-based FEA methods emerges due to the wide variation in spatial resolution and other imaging and reconstruction features among different CT scanners along with rapid upgrades in technology causing inconsistency in Tb micro-morphometric measures in multi-site and longitudinal bone studies (Chen et al 2018 ). Although, the paper by (Guha et al 2022 ) demonstrated that their method offers reliable measures of Tb microstructural strength at in vivo peripheral CT imaging, variability of their measures derived from muti-scanner CT images with varying spatial resolution has not yet been established. This paper is aimed to examine the multi-scanner variability of Guha et al ’s Tb FEA measures in an in vivo study.…”
Section: Introductionmentioning
confidence: 99%
“…Histomorphometric analysis of bone specimens is invasive, painful, and not feasible in routine clinical settings. There are a few non‐invasive techniques to assess bone microarchitecture such as micro‐magnetic resonance imaging (micro‐MRI), micro‐computed tomography (micro‐CT), and high‐resolution peripheral quantitative computed tomography (HRPqCT) 14 . These techniques are expensive and HRPqCT involves considerable radiation exposure.…”
Section: Introductionmentioning
confidence: 99%